The Effectiveness of Auditory Stimuli from Murottal Quran to Improve Comfort and Weight in Low Birth Weight Infants: Randomized Controlled Trial - Desriati Devi; Yeni Rustina; Defi Efendi (Universitas Airlangga, 2019)
Introduction: Low birth weight (LBW) infants who have been hospitalized are exposed to various conditions that provoke discomfort, which could trigger a stress response and growth disorders. This study aimed to identify the effects of auditory stimuli from Murottal Quran when it comes to the comfort and weight of LBW infants.Methods: This study used a clinical randomized controlled trial design involving 52 low birth weight infants. The infants were randomly assigned to either the intervention group (n=26) or the control (n=26). The intervention of Murottal Quran was given using a speaker 4 times a day for 20 minutes every 3 hours. This intervention was conducted for three days.Results: The results of this study show that there is a significant difference in the comfort of low birth weight infants after Murottal Qur’an on the first, second, and third days between the intervention and control groups (p=0.014; <0.001; <0.001). There was no significant difference in the weight between the intervention and control groups in the first, second, and third days (p=0.481; 0.481; 0.464).Conclusion: The auditory stimuli of Murottal Quran can help to improve the comfort level of low birth weight infants during hospitalization. It can therefore be used as a supportive therapy to facilitate low birth weight infant and premature infant development.